TRANSITIONING FROM THE STAGE TO THE BARRACKS: EXPLORING THE IMPACT OF MILITARY SERVICE ON BTS ARMY’S CONSUMER BEHAVIOR - Collantes, Franchesca Nicole; Hu, Guanlun; Delos Santos, Paula Sharmaine; Santiago, Isabelle; Ramos, Kristine Joy (WILAYAH: The International Journal of East Asian Studies, 2024)
BTS’ loyal fandom exists in the Philippines despite the geographic disparity and the language barrier and they have developed a fanatical attitude towards the group. All "able-bodied men" in South Korea, including members of BTS, are required to serve in the military for two years. This study seeks to examine the effect of the inactivity of BTS on Filipino ARMY but might have the intention to switch to other K-pop groups to idolize. The study is anchored in the Expectation Disconfirmation Theory and mainly employed a quantitative design. The results showed that Filipino ARMY’s Expectation and Hedonistic Consumption have a significant effect on Disconfirmation. Emotional Attachment was added as a moderating variable, and results showed that it has a significant moderating effect between Disconfirmation and Switching Intention. The study will benefit marketers as the results can give insights on how to sustain brand loyalty.